Video feedback in CBT supervision: review and illustration of two specific techniques. (14th October 2016) - Gonsalvez, Craig J.; Brockman, Robert; Hill, Hamish R. M.
Abstract: There is now expert consensus that directly observing the work of trainee therapists vs. relying upon self-report of sessions, is critical to providing the accurate feedback required to attain a range of competencies. In spite of this expert consensus however, and the broadly positive attitudes towards video review among supervisees, video feedback methods remain under-utilized in clinical supervision. This paper outlines some of the weaknesses that affect feedback based solely on self-report methods, before introducing some of the specific benefits that video feedback methods can offer the training and supervision context. It is argued that video feedback methods fit seamlessly into CBT supervision providing direct, accessible, effective, efficient and accurate observation of the learning situation, and optimizing the chances for accurate self-reflections and planning further improvements in performance. To demonstrate the utility of video feedback techniques to CBT supervision, two specific video feedback techniques are introduced and described: the Give-me-5 technique and the I-spy technique. Case examples of CBT supervision using the two techniques are provided and explored, and guidance as to the supervision contexts in which each of the two techniques are suitable, individually, and in tandem, are outlined. Finally, best practice guidelines for the use of video feedback techniques in supervision are outlined.